Antifungal piperamides from Piper mollicomum Kunth (Piperaceae) - da Silva, Herlle Aparecido; Yamaguchi, Lydia Fumiko; Young, Maria Cláudia Marx; Ramos, Clécio Souza; Amorim, André Márcio Araújo; Kato, Massuo Jorge; Batista, Ronan (Eclética Química, 2018)
The phytochemical study on dichlorometane extracts of leaves, stem and roots of Piper mollicomum Kunth (Piperaceae) led to isolation of the known piperamides tembamide (1), (R)-(-)-tembamide acetate (2) and riparin I (3). Compounds 1 and 2 displayed moderate in vitro antifungal activity against Cladosporium cladosporioides (5.0 μg) and Cladosporium sphaerospermum (1.0 μg) by direct bioautographic analyses and compound 3 was inactive up to 100.0 μg.